2009
DOI: 10.1590/s0101-60832009000600004
|View full text |Cite
|
Sign up to set email alerts
|

Coexistência das síndromes de Capgras e Frégoli associadas à redução de volume frontotemporal e hiperintensidades em substância branca cerebral

Abstract: Background: Delusional misidentification syndromes are conditions in which the patients pathologically misidentify people, places, objects or events. They have been categorized in four subtypes: Capgras, Frégoli, intermetamorphosis and subjective double syndromes. Such syndromes may be present in patients with psychiatric disorders such as schizophrenia and mood disorders, and with neurological diseases such as Alzheimer, Parkinson and brain injury (trauma, vascular). Objectives: To describe and discuss a case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Meta-analyses of delusional misidentification syndrome point to the involvement of the right frontal lobes (Atta et al 2006;Feinberg & Roane 2005), with other changes observed in the left temporal lobes (Edelstyn & Oyebode 1999;Feinberg et al 1999;Huang et al 1999;Signer 1994). Further, neuroimaging data in delusional misidentification syndrome and schizophrenia have demonstrated structural volume reduction in the frontotemporal area of the brain (Turkiewicz et al 2009), as well as reductions in structural magnetic resonance in the right frontal lobe (Coltheart et al 2007). A few studies showed damage to the right fusiform gyrus and para/hippocampal atrophy indicating temporal lobe deficiencies (Hudson 2000).…”
Section: Understanding Misidentification Syndromes Using the Integratmentioning
confidence: 99%
“…Meta-analyses of delusional misidentification syndrome point to the involvement of the right frontal lobes (Atta et al 2006;Feinberg & Roane 2005), with other changes observed in the left temporal lobes (Edelstyn & Oyebode 1999;Feinberg et al 1999;Huang et al 1999;Signer 1994). Further, neuroimaging data in delusional misidentification syndrome and schizophrenia have demonstrated structural volume reduction in the frontotemporal area of the brain (Turkiewicz et al 2009), as well as reductions in structural magnetic resonance in the right frontal lobe (Coltheart et al 2007). A few studies showed damage to the right fusiform gyrus and para/hippocampal atrophy indicating temporal lobe deficiencies (Hudson 2000).…”
Section: Understanding Misidentification Syndromes Using the Integratmentioning
confidence: 99%
“…Meta-analyses of delusional misidentification syndrome point to the involvement of the right frontal lobes (Atta et al 2006;Feinberg & Roane 2005), with other changes observed in the left temporal lobes (Edelstyn & Oyebode 1999;Feinberg et al 1999;Huang et al 1999;Signer 1994). Further, neuroimaging data in delusional misidentification syndrome and schizophrenia have demonstrated structural volume reduction in the frontotemporal area of the brain (Turkiewicz et al 2009), as well as reductions in structural magnetic resonance in the right frontal lobe (Coltheart et al 2007). A few studies showed damage to the right fusiform gyrus and para/hippocampal atrophy indicating temporal lobe deficiencies (Hudson 2000).…”
Section: Understanding Misidentification Syndromes Using the Integratmentioning
confidence: 99%
“…Meta-analyses of delusional misidentification syndrome point to the involvement of the right frontal lobes (Atta et al 2006; Feinberg & Roane 2005), with other changes observed in the left temporal lobes (Edelstyn & Oyebode 1999; Feinberg et al 1999; Huang et al 1999; Signer 1994). Further, neuroimaging data in delusional misidentification syndrome and schizophrenia have demonstrated structural volume reduction in the frontotemporal area of the brain (Turkiewicz et al 2009), as well as reductions in structural magnetic resonance in the right frontal lobe (Coltheart et al 2007). A few studies showed damage to the right fusiform gyrus and para/hippocampal atrophy indicating temporal lobe deficiencies (Hudson 2000).…”
mentioning
confidence: 99%